Students' perceptions and performances in academic essay writing in higher education - Hasegawa, Hiroshi (Australian Multicultural Interaction Institute, 2013)
All students who have completed their higher school certificate are expected to be both familiar with and equipped with the skills necessary for academic writing at university level. However, international students may experience various difficulties in this regard, deriving from linguistic, cultural, and/or social differences. International students must, therefore, develop and practise new skills and strategies if they are to write successfully at an academic level. Nevertheless, it is not unusual for lecturers to find that the academic writing of international students is better than that of some local students whose first language is English. This suggests that satisfactory academic writing is affected by factors other than just proficiency level in English. This paper uses the case study of one group of university students in Australia to investigate the impact of an introductory session about the lecturer's expectations for their academic writing on the students' actual writing performance. Data were collected from a questionnaire measuring the students' backgrounds and perceptions of their academic writing and a text analysis of their actual writing. This helped to identify factors that may contribute to the performance of each student in the writing of academic essays. It is anticipated that the findings of the study may assist educators to devise intervention strategies to support students in this area.